Home and Online Management and Evaluation of Blood Pressure (HOME BP) digital intervention for self-management of uncontrolled, essential hypertension: a protocol for the randomised controlled HOME BP trial. Issue 11 (7th November 2016) - Band, Rebecca; Morton, Katherine; Stuart, Beth; Raftery, James; Bradbury, Katherine; Yao, Guiqing Lily; Zhu, Shihua; Little, Paul; Yardley, Lucy; McManus, Richard J
Abstract : Introduction: Self-management of hypertension, including self-monitoring and antihypertensive medication titration, lowers blood pressure (BP) at 1 year compared to usual care. The aim of the current trial is to assess the effectiveness of the Home and Online Management and Evaluation of Blood Pressure (HOME BP) intervention for the self-management of hypertension in primary care. Methods and analysis: The HOME BP trial will be a randomised controlled trial comparing BP self-management—consisting of the HOME BP online digital intervention with self-monitoring, lifestyle advice and antihypertensive drug titration—with usual care for people with uncontrolled essential hypertension. Eligible patients will be recruited from primary care and randomised to usual care or to self-management using HOME BP. The primary outcome will be the difference in mean systolic BP (mm Hg) at 12-month follow-up between the intervention and control groups adjusting for baseline BP and covariates. Secondary outcomes (also adjusted for baseline and covariates where appropriate) will be differences in mean BP at 6 months and diastolic BP at 12 months; patient enablement; quality of life, and economic analyses including all key resources associated with the intervention and related services, adopting a broad societal perspective to include NHS, social care and patient costs, considered within trial and modelled with a lifetime horizon. Medication beliefs, adherence and changes; self-efficacy; perceived side effects and lifestyle changes will be measured for process analyses. Qualitative analyses will explore patient and healthcare professional experiences of HOME BP to gain insights into the factors affecting acceptability, feasibility and adherence. Ethics and dissemination: This study has received NHS ethical approval (REC reference 15/SC/0082). The findings from HOME BP will be disseminated widely through peer-reviewed publications, scientific conferences and workshops. If successful, HOME BP will be directly applicable to UK primary care management of hypertension. Trial registration number: ISRCTN13790648 ; pre-results.